2023
DOI: 10.1101/2023.04.26.538501
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of single-cell CRISPR perturbations indicates that enhancers act multiplicatively and provides limited evidence for epistatic-like interactions

Abstract: A single gene may be regulated by multiple enhancers, but how they work in concert to regulate transcription is poorly understood. Prior studies have mostly examined enhancers at single loci and have reached inconsistent conclusions about whether epistatic-like interactions exist between them. To analyze enhancer interactions throughout the genome, we developed a statistical framework for CRISPR regulatory screens that utilizes negative binomial generalized linear models that account for variable guide RNA (gR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
(117 reference statements)
0
5
0
Order By: Relevance
“…But, given the clustering or adjacency we observed in this list, and the fact that a lot of these genes are known to be regulated by super-enhancers according to dbSuper ( Hnisz et al 2013 ), we think these are indeed functional, but atypical EP pairs that function through a different mechanism that relies on the presence of other enhancers or promoters in the genomic neighborhood. A model where enhancers act multiplicatively to regulate a single gene was recently proposed ( Zhou et al 2023 ), and could potentially explain such pattern where a weak enhancer is functional near a stronger enhancer.…”
Section: Resultsmentioning
confidence: 99%
“…But, given the clustering or adjacency we observed in this list, and the fact that a lot of these genes are known to be regulated by super-enhancers according to dbSuper ( Hnisz et al 2013 ), we think these are indeed functional, but atypical EP pairs that function through a different mechanism that relies on the presence of other enhancers or promoters in the genomic neighborhood. A model where enhancers act multiplicatively to regulate a single gene was recently proposed ( Zhou et al 2023 ), and could potentially explain such pattern where a weak enhancer is functional near a stronger enhancer.…”
Section: Resultsmentioning
confidence: 99%
“…Our observations regarding super-additive effects of enhancers require particular care in interpretation. Previous studies have investigated how enhancers might combine additively, synergistically, or redundantly by assessing effects at the level of gene expression 39,[53][54][55][56][57] , cellular phenotypes 37 , or organismal phenotypes 58,59 . These studies have offered conflicting views, perhaps in part because these higher-order phenotypes might have varying non-linear relationships with quantitative gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In another separate study, GLiMMIRS was developed using negative binomial generalized linear models, accounting for sgRNA efficiency and several other covariates. Reanalysis of Gasperini's dataset [10] using this method, which investigated interactions between 3,808 enhancer pairs, showed that enhancers act in a multiplicative manner; however, the results provided no evidence for strong interactions between pairs of enhancers [53]. Most recently, SCREE has been introduced as a comprehensive workflow that facilitates crisprQTL data analysis.…”
Section: Computational and Statistical Toolkitsmentioning
confidence: 99%
“…As discussed above, despite the high efficiency of CRISPRi for perturbation across a cell population, it is susceptible to incomplete inhibition. The variability in sgRNA targeting efficacy and dCas9-KRAB perturbation should be considered [10], and GLiMMIRS uses a statistical model to account for this covariate [53].…”
Section: Pitfalls and Recommendationsmentioning
confidence: 99%